2019
DOI: 10.1590/0103-8478cr20190079
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linked coacervates of cashew gum and gelatin in the encapsulation of pequi oil

Abstract: Pequi oil is rich in bioactive compounds which can be encapsulated to increase protection against extrinsic environmental factors. A delayed degradation of pequi oil may occur by using microencapsulation technology, in addition to masking unpleasant flavors and aromas. Complex coacervation is a technique based on the electrostatic interaction between two oppositely charged biopolymers which form a matrix complexed around an agent of interest. However, cross-linking the particles is often necessary in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 41 publications
0
4
0
2
Order By: Relevance
“…40 Ideally, at the IEP, electrostatic interactions are reduced, but it has been reported that interactions with incorrect side types could form complexes. 41 Nascimento et al 39 evaluated a range of pH values, including the IEP of GEB for complexation with CG. The authors observed complex formation at pH 4.5 and 5.0.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Ideally, at the IEP, electrostatic interactions are reduced, but it has been reported that interactions with incorrect side types could form complexes. 41 Nascimento et al 39 evaluated a range of pH values, including the IEP of GEB for complexation with CG. The authors observed complex formation at pH 4.5 and 5.0.…”
Section: ■ Resultsmentioning
confidence: 99%
“…For polyelectrolyte complex formation, pH plays a key role in the extent of protein–polysaccharide interactions because it influences the degree of ionization of the functional groups present on the biopolymers . Ideally, at the IEP, electrostatic interactions are reduced, but it has been reported that interactions with incorrect side types could form complexes . Nascimento et al evaluated a range of pH values, including the IEP of GEB for complexation with CG.…”
Section: Resultsmentioning
confidence: 99%
“…Em trabalhos como o de Nascimento et al (2020) onde encapsularam o óleo de pequi em matriz de goma de cajueiro e gelatina, e de Alexandre et al (2019) utilizando as mesmas condições de formação da partícula, porém usaram o ácido tânico para a reticulação das partículas e o fortalecimento da matriz encapsulante a danos térmicos e mecânicos, foi obtido eficiência de encapsulamento (71%) não muito distante do obtido no trabalho de Nascimento (70%), tornando uma operação promissora em processos que buscam o enrijecimento da matriz encapsulante da partícula.…”
Section: Coacervaçãounclassified
“…In addition, beetroot betalains are marred by an earthy taste (Luiza Koop et al, 2022). Encapsulation technology is a well-known method to protect bioactive compounds from adverse conditions and mask unpleasant flavors/odors by forming a protective barrier with the encapsulated compound, thereby extending the shelflife of the substances and providing controlled release under specific conditions (Alexandre et al, 2019;Barroso et al, 2021).…”
Section: Introductionmentioning
confidence: 99%